ANALYSIS OF FOOD SECURITY LEVELS IN PADANG LAWAS DISTRICT - Muhammad Abduh Harahap; Zulkarnain Lubis; Syahbudin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Food security is a condition where food is met for the country as well as individuals, which is reflected in the availability of sufficient food, both in quantity and quality, safe, diverse, nutritious, equitable and affordable and does not conflict with the religion, beliefs and culture of the community, to be able to live a healthy life. , active and productive in a sustainable manner. This research aims. The method used in this research is descriptive qualitative and quantitative using the same analysis as the Food Security and Vulnerability Atlas of Indonesia (FSVA) 2009. This analysis of food security indicators consists of 3 indicators and 6 variables then entered into a formula, the results will be grouped based on 6 categories of food security and a food security map was created by calculating the composite index results for each of the 6 variables. The results of this research are the distribution of food security at the village level in Padang Lawas Regency, showing that in each village there are several categories of very resistant, resistant, moderately resistant, somewhat vulnerable and very vulnerable. Meanwhile, the condition of food security at the sub-district level is based on food availability, there are three sub-districts which are in the highly resilient category, namely Sihapas Barumun Subdistrict, Barumun Tengah Subdistrict and Huristak Subdistrict, and the food security condition is based on food affordability, namely all sub-districts in Padang Lawas are in the resilient category while it is based on utilization. Only one sub-district is considered food secure, namely Barumun Tengah sub-district. Meanwhile, a comparison of Padang Lawas district with other districts shows that Deli Serdang district is in first place, while the lowest or last place is Gunung Sitoli city, but Padang Lawas district is ranked 24th.